THE ROLE OF PEER GROUP EDUCATION IN IMPROVING BASIC LIFE SUPPORT (BLS) ABILITIES OF FARMERSIN LUMAJANG - Widianto, Eko Prasetya; Maisyaroh, Arista; Fibriansari, Rizeki Dwi (Universitas Wijaya Kusuma Surabaya, 2021)
Farmer-based agricultural nursing integrated emergency risk reduction is needed by increasing the ability of farmers. This study aimed to improve farmers’ basic life support (BLS) capacity using the peer group education approach in Lumajang Regency. This study’s design was a quasi-experimental design with a pre and post-test group design on 209 respondents. Bivariate analysis in this study used the Wilcoxon test to determine the effect of BLS ability before and after peer-group education. The majority of respondents were male, as many as 168 people (80.4%) with a productive age of 35-50, 94 people (45%), and a high school education level of 84 people (41%). Before mentoring was carried out, 72% in the low category increased to 56% having good abilities after being assisted BLS. The application of a peer group education approach is expected to improve safety in agricultural areas and minimize hazardous substances in the agricultural work environment. To improve the farmer’s ability about basic life support, not only with training methods, but it can be obtained from electronic media and print media regarding the application of basic life support.Keywords: Peer Group Education; Basic Life Support; Farmers